Enhancement of direct interspecies electron transfer and methane production by co-culture of dual Methanosarcina species and Geobacter metallireducens - Liu, Lu; Li, Pengsong; Dong, He; Liu, Chuanqi; Li, Haoyong; Ma, Zihao; Li, Ruoyu; Dang, Yan (Frontiers in Microbiology, 2025)
Anaerobic digestion is a key technology for converting organic waste into methane, offering significant potential for renewable energy production and waste management. While the addition of conductive materials has been shown to improve direct interspecies electron transfer (DIET), their application faces challenges like biofouling, environmental risks, and increased operational costs. This study investigated the effects of co-culturing dual Methanosarcina (Methanosarcina barkeri and Methanosarcina acetivorans) and Geobacter metallireducens (DM-G) to enhance DIET and methane production without the addition of exogenous conductive materials. The performance of the DM-G co-culture system was comparable to that of the conductive material-amended single Methanosarcina and G. metallireducens (SM-G) co-culture systems, achieving a maximum methane concentration of 19.5 mM, following the consumption of 15.2 mM ethanol in the 1:1:1 biomass ratio system. This corresponds to a 3.8-fold increase over the SM-G co-culture system with M. barkeri and G. metallireducens, and a 3.0-fold increase over that with M. acetivorans and G. metallireducens. Transcriptomic analysis showed that in the DM-G co-culture system, M. barkeri up-regulated key genes related to methane metabolism and acetate utilization, while the core methanogenic pathway of M. acetivorans was down-regulated, but it could still effectively utilize the electron transfer pathway, indicating metabolic complementarity. These findings propose a novel strategy for enhancing DIET-driven methanogenesis through synergistic microbial consortia, advancing scalable, low-cost bioenergy solutions for organic waste valorization.